Analysis of Indoor Air Quality in the Laboratories of Poltekkes Riau - Nopriandi, Nopriandi; Zulherman, Zulherman; Tela, I Nengah; Kusumah, Dadang Puja (Journal of Architectural Research and Design Studies, 2026)
This study examines indoor air quality (IAQ) in Poltekkes Riau's laboratory building through systematic measurement of six parameters: CO₂, HCHO, TVOC, PM1.0, PM2.5, and PM10 per Minister of Health Regulation No. 48/2016. Direct measurements were conducted in ten laboratories under three operational conditions (active use, no activity, ventilation shutdown) across different time intervals. Results reveal significant deviations from standards: 60% of spaces exceeded CO₂ limits during active use, while PM2.5 and PM10 exceeded thresholds in 90% of measured spaces. Notably, 70% of rooms exceeded formaldehyde limits and 80% exceeded TVOC limits, particularly in spaces with MDF materials. Original findings document passive off-gassing phenomena where formaldehyde peaked during non-occupancy periods, and establish correlations between architectural features and multi-pollutant accumulation. Recommendations include strategic exhaust fan placement, low-VOC materials, and cross-ventilation systems for tropical educational environments, supporting the urgent need for updated building regulations addressing multi-pollutant environments in health education facilities.